2019
DOI: 10.5005/jp-journals-10047-0074
|View full text |Cite
|
Sign up to set email alerts
|

Use of Resin Solvent as a Facilitator for Removal of Resin Composite Restoratives by Influencing their Mechanical Properties: Is this Possible?

Abstract: Aim:The aim is to evaluate the influence of resin solvent on Vickers microhardness, flexural strength, and flexural modulus of a resin composite in order to test the ability of resin solvent to soften or weaken resin composite during replacement of failed restoration. Materials and methods: Fifty specimens were prepared from Tetric N-Ceram; forty used for flexural strength and elastic modulus tests and ten used for microhardness test. For flexural strength; they were divided into four groups of ten specimens e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition, trials to use resin solvents to aid in the removal of failed resin composite restoration have been attempted. It was found that resin solvents have the potential to reduce the flexure strength of resin composite 5 . In another study, it was found that resin solvent stained resin composite which might help in its identification from tooth structure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, trials to use resin solvents to aid in the removal of failed resin composite restoration have been attempted. It was found that resin solvents have the potential to reduce the flexure strength of resin composite 5 . In another study, it was found that resin solvent stained resin composite which might help in its identification from tooth structure 6 .…”
Section: Introductionmentioning
confidence: 99%